(3QSGdI aj GdJaSjQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3gs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; gPg JUOjQ eHGQc CdbjJg jhe CLdSJ ddJOQjS HLGeY TjNh HYO GdHSedI GdMeO ddg GdPj Ndb GdSeGhGJ hGdCQV CeG HYO abO bGd Gddg JYGdi EfG aJMfG dc aJMG eHjfG djZaQ dc eG JbOe ef PfHc s
(3BNQgG (B:s
(3CfTOfj CHh HcQ YHjO Gddg Hf MejO GdeQOH QH Pj fVhHG ef GdYGde TQg dG jQi EdG ZfjG hgh dG jedc PQI Ke dh CbSe aj TjA Ydi Gddg dCHQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs